Widely Targeted Metabolomics Analysis of Dendrobium officinale at Different Altitudes. Issue 4 (23rd March 2023) - Jia, Xiaohuan; Wu, Faming; Lu, Anjing; Tan, Daopeng; Zhang, Qianru; He, Yuqi; Qin, Lin
Abstract: In order to investigate the differences in the chemical composition of Dendrobium officinale at different altitudes, we collected Dendrobium officinale from different altitudes in Guizhou Province, China, and firstly determined its polysaccharide content by using a sulfuric acid‐phenol color development method with reference to the Chinese Pharmacopoeia, and further determined its metabolites by using widely targeted metabolomics, and explored the differences in the chemical composition of Dendrobium officinale at different altitudes using multivariate statistical analysis. We found that the polysaccharide content was higher in plants growing at 1122 m, a total of 902 secondary metabolites were detected by wildly targeted metabolomics, and amino acids and their derivatives were more highly expressed at 1122 m, while other metabolites were more highly expressed at 835 m. Furthermore, we found that the phenolic acid compound nerugein was only present in plants at 835 m, and two lipid compounds, namely Lyso PE 20 : 4 and its isomer, were only present at 1122 m. Taken together, these results may provide a basis for the selection and clinical application of D. officinale cultivated at different altitudes. Abstract :